Korelasi hs-CRP dan Keberadaan Staphylococcus aureus pada Luka Gangren Diabetes Mellitus Tipe II - Sri Wahyuni; Fathul Hidayatul Hasanah; Binti Mu’arofah; Verdyan Taufan Rizky Jeferson (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Diabetes mellitus (DM) is a metabolic disorder that is accompanied  by an increased glucose in the blood or called hyperglycemia. Diabetes can be caused by problems with the pancreas not being able to produce insulin, insufficient insulin secretion, imperfect insulin action, or both. When blood glucose is left elevated for a long time, it can cause complications such as gangrene. Diabetic gangrene is one of the complications caused by tissue damage. Gangrene occurs due to neuropathy and vascular disorders, usually in the peripheral areas of the body. Bacteria found in diabetic wounds are bacteria that produce biofilms such as Staphylococcus aureus. Staphylococcus aureus can release exotoxins such as leukocidin. Leucosidine lyses PMNs and releases ROS which will then induce a cytokine response such as interleukin-6 which will increase CRP levels. hs-CRP is a high precision CRP measurement even at low concentrations.This study aims to determine the correlation between hs-CRP levels and the presence of Staphylococcus aureus in type II diabetes mellitus gangrene wounds. The research design used is observational analytical using a cross sectional approach and accidental sampling. There were 16 research respondents with increased hs-CRP levels in 15 respondents and 9 respondents with Staphylococcus aureus bacteria. Correlation test with a value of p = <0.05 (p=0.032) means that there is a correlation between hs-CRP and the presence of Staphylococcus aureus in type II diabetes mellitus gangrene wounds.